Smart health informatics system - Nguyen P.T.; Ilayaraja M.; Shankar K.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The smart health informatics system give data about health, compilation, analyses and generation also provide secure data for system development and safe policy. Health informatics system in relies upon quality, cost and efficiency of healthcare system. The smart health informatics system has positive influences on health but some failures and difficulties are there, that need to concern in future research. For better coordinate of Healthcare the smart health informatics system consider as an important component. This system emphasis on proper transmission, retrieval, generation and storage of health data. A good decision making is necessary for making a relevant, timely health and accurate smart health informatics system. BEIESP.